Gambaran Pengetahuan dan Health Seeking Behaviour pada Penderita Diabetes Melitus Tipe 2 - Rusmayanti, Putu Siska Ayu; Manto, Onieqie Ayu Dhea; Santoso, Bagus Rahmat (Jurnal Gema Keperawatan, 2024)
Diabetes mellitus is a non-communicable disease that currently represents a public health problem. Diabetes mellitus diseases caused by the inability of the pancreas to produce enough insulin (a hormone that manages glucose or sugar in the blood) or the inability of the body to manage the insulin produced effectively. The incidence of diabetes mellitus is increasingly concerning because the number has increased by year to year. Patients with DM and their families are expected to further increase knowledge of management and control of diabetes mellitus and improve health seeking behavior. This study aims to determine and identify the knowledge and health seeking behavior of patients with type 2 diabetes mellitus. This study uses quantitative methods with a cross-sectional approach. The sampling technique used purposive sampling, the sample size was 54 people. The analysis test used univariate analysis. This research instrument is a knowledge level questionnaire and a health seeking behavior questionnaire. The results of the study, the knowledge of patients with type 2 diabetes mellitus in the good category amounted to 55,6% and health seeking behavior in the good category amounted to 61,1%. The conclusion of this study is that patients at the Banjarmasin Terminal Health Center have good knowledge and health seeking behavior. The community, especially type 2 diabetes patients, is expected to continue to increase knowledge and awareness of health problems and encourage healthy behavior